2019
DOI: 10.1590/0366-69132019653732573
|View full text |Cite
|
Sign up to set email alerts
|

Controlling sintering and grain growth of nanoceramics

Abstract: Sintering and grain growth are fundamental processes affecting microstructural evolution of ceramics. The phenomenological models describing these processes as found in textbooks are simplifications of the very dynamic set of system’s parameters, which lead to limited predictability and the need for extensive empirical analyses for process optimization. One such simplification is the underestimation of interfacial energies and their relationships with diffusion paths and growth control. The goal of this paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…The 2°. An increase in dihedral angle can be interpreted as an increase in sintering stress 34 , which is aligned with the previous discussion on the effect of Mn on sintering 18 . That is, the fact that the grain boundary energy is dramatically reduced favors grain boundary formation at the initial stages of sintering, while de-stabilizing isolated pores at the final stage, whose stability is directly dependent on dihedral angles 53 .…”
Section: Author Manuscriptsupporting
confidence: 90%
See 1 more Smart Citation
“…The 2°. An increase in dihedral angle can be interpreted as an increase in sintering stress 34 , which is aligned with the previous discussion on the effect of Mn on sintering 18 . That is, the fact that the grain boundary energy is dramatically reduced favors grain boundary formation at the initial stages of sintering, while de-stabilizing isolated pores at the final stage, whose stability is directly dependent on dihedral angles 53 .…”
Section: Author Manuscriptsupporting
confidence: 90%
“…While the mechanism of the dopant effects is still under debate and is so far system specific, it is generally accepted that dopants can change interfacial energies and/or affect diffusion mechanisms. While doping effects on diffusion mechanisms have been discussed for years 17 , only more recently the role of interfacial energies on sintering and microstructural evolutions has been demonstrated to be very relevant both experimentally 18,19 and by modelling 20 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been thus suggested that the actual effect of additives on the chemical potential differences will dictate the effectiveness of a dopant. 66 In alignment with Lange et al's theories of thermodynamics of sintering, an increase in dihedral angle shall cause an increased driving force for mass flow towards neck formation and densification. 27 The relevance of the dihedral angle on densification has been demonstrated in SnO 2 by Chang et al 67 It was shown that a change in the dihedral angle as small as 7° can reverse the mass flow from a non-densification to a densification mechanism.…”
Section: Insights On Sintering Controlmentioning
confidence: 71%
“…It has thus been proposed that sintering can be slowed down by increasing the grain boundary energy and decreasing the surface energy itself. This would lead to an increase in the interface energy equilibrium angle at the contact of two particles, known as the dihedral angle, retarding the coalescence of particles regardless of the mass transport mechanism …”
Section: Introductionmentioning
confidence: 99%
“…This would lead to an increase in the interface energy equilibrium angle at the contact of two particles, known as the dihedral angle, retarding the coalescence of particles regardless of the mass transport mechanism. 15 There are only a few experimental studies on the measurement of surface energy in zinc aluminate spinel. Quach et al have reported the room-temperature anhydrous surface energy of ZnAl 2 O 4 by water adsorption microcalorimetry as 1.36 J/m 2 .…”
Section: Introductionmentioning
confidence: 99%